Penggunaan Media Pembelajaran Chat Sonic dalam Pembelajaran Teks Prosedur pada Siswa Kelas XI Sekolah Menengah Atas - Rizal, Mohammad Khoirul; Alatas, Mochamad Arifin (Universitas Sebelas Maret, 2025)
This study is motivated by the low level of student participation and understanding in procedural text learning, largely due to the continued use of conventional teaching methods that are less responsive to the learning characteristics of the digital-native generation. Meanwhile, the use of artificial intelligence-based media—such as ChatSonic—in Indonesian language learning remains limited. This research aims to describe the use of ChatSonic as an instructional medium for teaching procedural texts to eleventh-grade high school students and to assess its effectiveness in three main aspects: (1) improving students’ understanding of the structure and linguistic features of procedural texts, (2) encouraging students’ ability to compose procedural texts in a coherent and systematic manner, and (3) increasing student participation and enthusiasm during the learning process. The study employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The findings are expected to contribute to the development of adaptive and relevant technology-based learning media in the context of 21st-century education.Penelitian ini dilatarbelakangi oleh rendahnya partisipasi dan pemahaman siswa dalam pembelajaran teks prosedur akibat masih dominannya penggunaan metode konvensional yang kurang responsif terhadap karakteristik belajar generasi digital. Sementara itu, pemanfaatan media berbasis kecerdasan buatan, seperti ChatSonic, dalam pembelajaran Bahasa Indonesia masih sangat terbatas. Penelitian ini bertujuan untuk mendeskripsikan penggunaan ChatSonic sebagai media pembelajaran teks prosedur pada siswa kelas XI SMA serta menilai efektivitasnya dalam tiga aspek utama: (1) meningkatkan pemahaman siswa terhadap struktur dan ciri kebahasaan teks prosedur, (2) mendorong kemampuan menyusun teks prosedur secara runtut dan sistematis, dan (3) meningkatkan partisipasi dan antusiasme belajar siswa. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Temuan dalam penelitian ini diharapkan dapat memberikan kontribusi bagi pengembangan media pembelajaran berbasis teknologi yang adaptif dan relevan dengan kebutuhan pendidikan abad ke-21.